TROMBOSIT TERENDAH, KENAIKAN HEMATOKRIT DAN KADAR TNF-Î± SEBAGAI INDIKASI KEPARAHAN INFEKSI VIRUS DENGUE PADA PASIEN DD DAN DBD - A.S. Siskayani; I Made Sumarya; N.L.P Kartika Sari (UNHI Press, 2019)
Clinical manifestations of dengue virus infection vary from unspecified fever, dengue fever (DF) and dengue hemorrhagic fever (DHF). The fundamental difference in the diagnosis between DF and DHF is plasma leakage, hypotension, thrombocytopenia and hemorrhagic diathesis in DHF. The objectives of the study were to determine the lowest platelet, haematocrit increase, and TNF-Î± levels in DF and DHF patients as an indication of severity of dengue virus infection. The cross-sectional study was conducted by taking 54 blood samples of patients aged 26-45 years who were infected by dengue virus and grouped into two groups: DF patient group (27 blood samples) and DHF group (27 blood samples). The lowest platelets and hematocrit rise were determined by Hematology Analyzer and the TNF-Î± levels were determined by ELISA. The data obtained were statistically analyzed by independent Mann-Whitney test. The results showed that the lowest mean platelet counts of DF patients were significantly (p <0.01) higher than those of DHF patients. The mean hematocrit increase in DF patients was significantly (p <0.01) lower than that of the DHF patients and the mean TNF-Î± levels of DF patients were significantly (p <0.01) lower than the DHF patients. Based on the results of this study it can be concluded that the lowest platelets, hematocrit increase and TNF-Î± levels are an indication of the severity of dengue virus infection.